Universal preprocedural SARS-CoV-2 testing protocol within a large healthcare system. Issue 10 (9th August 2021) - Squiers, J J; Ghamande, S; Qiu, T; Robinson, C; Bertschy, C; Arroliga, A C; Peters, W
Abstract : This research letter details the safety of a universal asymptomatic preprocedural SARS-CoV-2 testing protocol implemented within a large, integrated healthcare system. Among over 145 000 tests administered, fewer than 1 in 1000 patients had subsequent positive tests within 10 days of an initial negative SARS-CoV-2 test. Despite the infrequency of positive tests after negative screening tests, patient-to-provider transmission was documented in five instances.